Effects of Integrated Nutrition-Specific and Nutrition-Sensitive Interventions on Child Growth Outcomes in Low- and Middle-Income Countries: A Systematic Review - Nuraini, Dwi Lisa; Ramadianti, Dita Tri; Syukrina, Fatma (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2025)
Child undernutrition and poor linear growth remain major challenges in low- and middle-income countries (LMICs). Integrated approaches combining nutrition-specific interventions—such as infant and young child feeding (IYCF), supplementation, and counseling—with nutrition-sensitive components including agriculture, cash transfers, WASH, and behavior-change communication are widely promoted, but their effectiveness remains inconsistent. This systematic review, conducted according to PRISMA 2020 guidelines, synthesized evidence from cluster randomized trials, randomized controlled trials, and quasi-experiments evaluating child growth outcomes in LMICs (HAZ, LAZ, WAZ, WHZ). Searches across PubMed, Google Scholar, Cochrane CENTRAL, and OpenAlex identified 4,041 records, from which 12 studies met inclusion criteria; meta-analysis was not performed due to heterogeneity. Nutrition-specific interventions, particularly IYCF and home-based health promotion, improved developmental outcomes and modestly enhanced linear growth (e.g., Tanzania: cognitive SMD 0.15 [95% CI 0.05–0.24]; motor 0.16 [0.03–0.28]). Facility-based counseling increased exclusive breastfeeding (+12.8 pp [2.1–23.6]) and feeding frequency (+14.1 pp [9.0–19.2]) without significant anthropometric effects. Agriculture plus behavior-change programs improved diet quality and growth (Ethiopia: HAZ +0.28 [0.02–0.54]; Ghana: β≈0.40–0.44). WASH-only interventions in Bangladesh, Zimbabwe, and Cambodia showed minimal impact on growth. Integrated nutrition-specific and nutrition-sensitive programs yield modest but meaningful gains in linear growth, particularly with high program intensity and caregiver participation, whereas household-level WASH interventions alone are insufficient. Future efforts should emphasize harmonized intervention frameworks and standardized outcome measures to strengthen comparability and policy relevance.